The test accuracy of antenatal ultrasound definitions of fetal macrosomia to predict birth injury: A systematic review. (March 2020) - Robinson, Rebecca; Walker, Kate F.; White, Victoria A.; Bugg, George J.; Snell, Kym I.E.; Jones, Nia W.
Abstract: Objectives: To determine which ultrasound measurement for predicted fetal macrosomia most accurately predicts adverse delivery and neonatal outcomes. Study Design: Four biomedical databases searched for studies published after 1966. Randomised trials or observational studies of women with singleton pregnancies, resulting in a term birth who have undergone an index test of interest measured and recorded as predicted fetal macrosomia ≥28 weeks. Adverse outcomes of interest included shoulder dystocia, brachial plexus injury (BPI) and Caesarean section. Results: Twenty-five observational studies (13, 285 participants) were included. For BPI, the only significant positive association was found for Abdominal Circumference (AC) to Head Circumference (HC) difference > 50 mm (OR 7.2, 95 % CI 1.8–29). Shoulder dystocia was significantly associated with abdominal diameter (AD) minus biparietal diameter (BPD) ≥ 2.6 cm (OR 4.2, 95 % CI 2.3–7.5, PPV 11 %) and AC > 90th centile (OR 2.3, 95 % CI 1.3–4.0, PPV 8.6 %) and an estimated fetal weight (EFW) > 4000 g (OR 2.1 95 %CI 1.0–4.1, PPV 7.2 %). Conclusions: Estimated fetal weight is the most widely used ultrasound marker to predict fetal macrosomia in the UK. This study suggests other markers have a higher positive predictive value for adverse outcomes associated with fetal macrosomia.